2022
DOI: 10.3390/su15010452
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organizational Democracy on Organizational Citizenship Behaviors in Digital Transformation: Mediating Effects of Job Satisfaction and Organizational Commitment for Smart Services

Abstract: This study investigated the influence of organizational democracy on organizational citizenship behaviors in digital transformation, by considering the mediating effects of job satisfaction and organizational commitment for smart services. Exploratory factor analysis (EFA) was conducted to investigate the factors, which was followed by confirmatory factor analysis (CFA) and path analysis to test the hypotheses. The sample consisted of 144 full-time employees of the largest bank in North Cyprus. The findings su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
(118 reference statements)
0
4
0
1
Order By: Relevance
“…They found that SMC has a significant socialization potential linked to a harmonious working environment in terms of democracy and SMC. Haskasap et al (2023) research results show that organizational democracy has a significant, positive, direct effect on job satisfaction and organizational commitment, but its direct effect on organizational citizenship behaviors is not significant. Ahmed et al (2019) conducted research to reveal the effects of organizational democracy on employee outcomes (commitment, citizenship behaviour and turnover intention) through the mediating role of organizational justice.…”
Section: Literature Reviewmentioning
confidence: 79%
See 1 more Smart Citation
“…They found that SMC has a significant socialization potential linked to a harmonious working environment in terms of democracy and SMC. Haskasap et al (2023) research results show that organizational democracy has a significant, positive, direct effect on job satisfaction and organizational commitment, but its direct effect on organizational citizenship behaviors is not significant. Ahmed et al (2019) conducted research to reveal the effects of organizational democracy on employee outcomes (commitment, citizenship behaviour and turnover intention) through the mediating role of organizational justice.…”
Section: Literature Reviewmentioning
confidence: 79%
“…Organizational democracy is defined as the process of dividing the power held by business owners or managers by including their employees in the decision-making process. When the concept of organizational democracy is evaluated as a process, it ensures the involvement of employees in business processes and their satisfaction, increased participation and innovation, and ultimately an increase in the performance of the organization (Bilge et al, 2020;Haskasap et al, 2023). Although the main idea of the concept of organizational democracy includes employees in managerial activities, studies have shown that this understanding is not sufficient or incomplete to fully express the concept of organizational democracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although it is the most commonly applied in the UK with many cases are available through Jisc, there remains little peer-reviewed published research into the way it has been applied (see Foster et al ., 2023). Evidence does, however, highlight how an organisation’s climate for shared decision-making influences how employees voluntarily contribute or share new ideas during digital transformation (Haskasap et al ., 2023) and how executives' business, technical and financial connections can support (or otherwise) digital transformation efforts (Bai et al ., 2023). This evidence highlights it is reasonable to expect variations in the engagement of the framework in higher education, partly depending on its fit with existing cultures and the style of the that engagement over time (also see Huber et al ., 2023).…”
Section: Reflections On Applicationmentioning
confidence: 99%
“…(Akbar et al, 2019) OCB adalah perilaku individu yang secara sukarela dilaksanakan untuk mendukung organisasi dan tanpa mengharapkan imbalan atau penghargaan dari organisasi dengan indikatornya, yaitu: a) kesadaran, b) kesopanan, c) kebajikan sipil, d) altruisme, dan e) sportivitas. (Haskasap et al, 2023) OCB adalah perilaku sukarela yang diberikan individu kepada organsiasi untuk menciptakan efektivias dan keberlangsungan organisasi tanpa adanya pengharapan dalam bentuk imbalan ataupun penghargaan, dalam hal ini bersifat tanpa pamrih dan sekedar memberikan kontribusi pada organsiasi. (Knezović & Smajić, 2022) OCB dapat menjadi mediasi kepemimpinan transformasioanal dimana seorang pemimpin hendaknya memberikan motivasi dan contoh teladan kepada bawahan sehingga perilaku kewargaan organisasi menjadi meningkat, dengan demikian bawahan akan dapat bekerja secara optimal.…”
Section: Kepemimpinan Transformasionalunclassified